Analysing the print media coverage of professional tennis players: British newspaper narratives about female competitors in the Wimbledon Championships. (12th February 2007) - Vincent, John; Pedersen, Paul M.; Whisenant, Warren A.; Massey, Dwayne
This study examined 152 articles devoted to female tennis players competing in the 2000 Wimbledon Championships in The Times, Daily Mail, and The Sun, covering a 17-day period that coincided with the Wimbledon Championships fortnight. Based upon the theoretical framework of gender power relations, a qualitative textual analysis methodology was used to reveal recurring themes within the dominant discourse about female tennis players. Results indicate the narratives used by the predominantly male journalists devalued, marginalised, and trivialised the athleticism of the female tennis players. The British newspapers seemed equally infatuated with Anna Kournikova, who was portrayed as a kind of sporting Lolita, and her hyper-feminine peers, the 'heterosexual honeys'. In contrast, Serena and Venus Williams – the 'Amazons' – were subjected to racial bigotry. The racial distinctions suggested that the hegemonic standard of the media was a favourable bias towards White female athletes. The sociological implications of such coverage of professional female tennis players are also discussed.